2016
DOI: 10.1175/jpo-d-15-0132.1
|View full text |Cite
|
Sign up to set email alerts
|

Scalings for Submarine Melting at Tidewater Glaciers from Buoyant Plume Theory

Abstract: Rapid dynamic changes at the margins of the Greenland Ice Sheet, synchronous with ocean warming, have raised concern that tidewater glaciers can respond sensitively to ocean forcing. Understanding of the processes encompassing ocean forcing nevertheless remains embryonic. The authors use buoyant plume theory to study the dynamics of proglacial discharge plumes arising from the emergence of subglacial discharge into a fjord at the grounding line of a tidewater glacier, deriving scalings for the induced submarin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
167
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(178 citation statements)
references
References 54 publications
10
167
1
Order By: Relevance
“…[47]). Modelling studies indicate that submarine melt rate increases linearly with water temperature and with the subglacial discharge of meltwater runoff raised to a power between one-third and three-fourths [48][49][50], supporting the interpretation of these highly undercut zones as areas of enhanced plume-driven melting. [23] and Bevan et al [17], supplemented with additional data from digitisation of Landsat scenes.…”
Section: Processes Of Frontal Ablationmentioning
confidence: 75%
“…[47]). Modelling studies indicate that submarine melt rate increases linearly with water temperature and with the subglacial discharge of meltwater runoff raised to a power between one-third and three-fourths [48][49][50], supporting the interpretation of these highly undercut zones as areas of enhanced plume-driven melting. [23] and Bevan et al [17], supplemented with additional data from digitisation of Landsat scenes.…”
Section: Processes Of Frontal Ablationmentioning
confidence: 75%
“…Xu et al (2013) detected that this relationship of melt rate to thermal forcing depends on the amount of subglacial discharge released through a single channel at a tidewater glacier: the melt rate dependence to temperature has a power of 1.76 for small discharges and is lower for higher discharge. Slater et al (2016) found a power law dependence of melt rate on discharge, with the exponent 1/3 for both the CP and the LP models in a uniform stratification. For a linear stratification their study shows that the exponent enlarges to 3/4 for the CP model and to 2/3 for the LP model.…”
Section: Introductionmentioning
confidence: 90%
“…A model based upon one-dimensional plume theory (e.g. Jenkins, 2011;Carroll et al, 2015;Slater et al, 2016) would be less computationally expensive and may allow some of these limitations to be addressed. However, such a model would not capture the strong surface currents driven by the plume which are important for the terminus morphology studied here.…”
Section: Plume Model and Undercuttingmentioning
confidence: 99%